Axial ligand effect on the stability of Fe–N–C electrocatalysts for acidic oxygen reduction reaction. (December 2020) - Wang, Feiteng; Zhou, Yipeng; Lin, Sen; Yang, Lijun; Hu, Zheng; Xie, Daiqian
Abstract: Iron and nitrogen co-doped carbons (Fe–N–C) have comparable activity to Pt-based catalysts for oxygen reduction reaction (ORR), but with much poorer durability in acidic electrolytes. Recently, regulating the coordination environment of Fe center (in-plane or axially) to boost the ORR activity of Fe–N–C has attracted many interests, and the axial OH ligand is even regarded as a necessary part of a highly-active structure. However, the influence of these regulations on the stability is still not clear. Herein, we performed kinetic and thermodynamic calculations based on density functional theory with explicit consideration of electrode potential to study the OH axial ligand effect on the stability of Fe–N–C electrocatalysts. We found that although the OH ligand can enhance the ORR onset potential to some extent, it substantially increases the H2 O2 selectivity, pushing ORR diverted to the 2e- + 2e-pathway. In the latter 2e-process (H2 O2 reduction), harmful hydroxyl radicals could be produced upon H2 O2 dissociation. Therefore, from the perspective of catalysts' stability, OH ligand coordination on the metal center is not a good way to develop stable ORR catalysts. Graphical abstract: We report a theoretical study of the axial ligand effect on the stability of Fe–N–C electrocatalyst for acidic oxygen reduction reaction. Even though axial ligand could promote the ORR activity, it could also increase H2 O2 selectivity. The generated H2 O2 might turn into harmful hydroxyl radicals (OH) on the Fe-based active sites through Fenton-like reactions. Therefore, from the perspective of long-term stability, axial ligand coordination on the metal center is not a good way to develop stable ORR catalysts. Image 1 Highlights: Potential and solvent are explicitly included in a first-principles kinetic modeling of the degradation of Fe–N–C during ORR. Axial OH ligand on the metal center of Fe–N–C is unfavorable for catalysts' stability due to much increased H2 O2  selectivity. At high potential, Fe–N–C sites may induce Fenton-like reactions to produce harmful hydroxyl radicals (OH) from H2 O2 . The dual metal sites in Fe–N–C can suppress H2 O2  production, thus is a promising direction for stability enhancement.